2018
DOI: 10.1007/s00392-018-1260-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cardiovascular complications in chronic kidney disease: research focus of the Transregional Research Consortium SFB TRR219 of the University Hospital Aachen (RWTH) and the Saarland University

Abstract: Patients with chronic kidney disease (CKD) exhibit a massively increased risk for cardiovascular (CV) events, and traditional strategies to improve CV outcome have largely failed in the context of CKD. This review article summarizes the current understanding of the pathophysiology of CVD in patients with CKD, defines the gaps in knowledge and describes the structure of the German Transregional Research Consortium SFB TRR219 which addresses "Mechanisms of Cardiovascular Complications in Chronic Kidney Disease".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…The prospective COMBO Stent registry, for instance, included 3614 patients and documented TLF in 3.9%, cardiac death in 1.6%, and definite stent thrombosis in 0.5% (versus 3.3%, 1.4%, and 0.4% herein) [25][26][27][28][29][30]. Although complication rates were relatively low in general, patients with CKD had a higher risk of major and minor bleeding as well as access site-related complications leading to prolonged hospitalization and higher rates of end points at discharge (supplement Table 1), which is in line with previous publications [28][29][30][31][32]. Bleeding occurred in 2.3% of all included patients, with twofold higher rates of minor and major bleeding in CKD.…”
Section: Discussionsupporting
confidence: 87%
“…The prospective COMBO Stent registry, for instance, included 3614 patients and documented TLF in 3.9%, cardiac death in 1.6%, and definite stent thrombosis in 0.5% (versus 3.3%, 1.4%, and 0.4% herein) [25][26][27][28][29][30]. Although complication rates were relatively low in general, patients with CKD had a higher risk of major and minor bleeding as well as access site-related complications leading to prolonged hospitalization and higher rates of end points at discharge (supplement Table 1), which is in line with previous publications [28][29][30][31][32]. Bleeding occurred in 2.3% of all included patients, with twofold higher rates of minor and major bleeding in CKD.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, a pilot study revealed that CXCR4-directed 68 Ga-Pentixa for PET/CT identified more lesions than 18 F-FDG PET/CT [74]. In addition, 111 In-DOTA-DAPTA (CCR5 antagonist) has been shown to detect atherosclerotic lesions in Apoe − /− mice, suggesting that 111 In-DOTA-DAPTA can specifically target CCR5 in atherosclerotic lesions [75]. All these findings suggest that chemokines and chemokine like mimetics may be useful to assess individual atherosclerotic burden, as a surrogate marker for CAD screening or a predictor of clinical cardiovascular events and may function as imaging tracers for a better understanding of characteristics of atherosclerotic lesions.…”
Section: Biomarkers and Imaging Tools For Diagnosis And Prognosismentioning
confidence: 99%
“…CV calcification could be one of the key mechanisms leading to increased CVD in Modifications in the circulation as well as in the myocardium are crucially involved in the increased CV risk in CKD patients. However, both the mediators and the underlying molecular mechanisms remain largely unexplored [12]. CV calcification-both in the tunica intima and in the media-is massively increased in CKD patients and is an independent risk factor for CV morbidity and mortality [13].…”
Section: Introductionmentioning
confidence: 99%